KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X MAN I KINALI KABUPATEN PASAMAN BARAT - Nursaid, Nuraini Eka Putri, Yasnur Asri, (Universitas Negeri Padang, 2017)
This article was written to describe the contribution of reading comprehension skills of exposition texts to the skills of writing exposition of students of class X MAN I Kinali Pasaman Barat. This research type is quantitative research by using descriptive method. The research design used is the correlational contribution of two variables. The population of this study is students of class X MAN I Kinali West Pasaman Regency registered in academic year 2016/2017 with the number of 108 students spread in five classes. The sample in this study amounted to 35 people. Samples were taken using a simple random technique with a precision of 15% using the Taro Yamane formula. The instrument of this research is performance test, that is writing of expository text writing and objective test of reading comprehension text of exposition. The results of this study there are three. First, the skill of writing exposition of the students of class X MAN I Kinali West Pasaman Regency is in more than enough qualification. Second, the reading comprehension skills of expository texts of grade X MAN I Kinali of Pasaman Barat Regency are in more than enough qualification. Third, based on the result of t-test, it can be concluded that reading comprehension skills of exposition texts contribute to the expository writing skill of MAN I Kinali students of Pasaman Barat Regency.Â Kata kunci: kontribusi, keterampilan, membaca, menulis,Â teks eksposisi